2020
DOI: 10.12963/csd.20734
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy of Dysarthria in Patients with Multiple System Atrophy using Water Resistance Therapy

Abstract: Objectives: Multiple System Atrophy (MSA) is atypical parkinsonian syndrome (APS) affecting respiration, phonation, resonance, and articulation, which is characterized by a mixed type of dysarthria involving hypokinetic, ataxic and spastic. However, there are still very limited speech interventions for MSA, and these demonstrate contrasting effects. The purpose of this study was to investigate the efficacy of water resistance therapy (WRT) of dysarthria in patients with multiple system atrophy. Methods: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The results for reading intelligibility were promising and in line with other therapies [ 24 , 27 , 29 ]. The results were less clear for the monologue task due to variable performance of participants.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results for reading intelligibility were promising and in line with other therapies [ 24 , 27 , 29 ]. The results were less clear for the monologue task due to variable performance of participants.…”
Section: Discussionsupporting
confidence: 75%
“…Together these studies have highlighted a range of potential communication benefits across all areas of the International Classification of Functioning and Disability (ICF) model, i.e., impairment (e.g. breath support, voice quality, loudness [23][24][25][26][27][28]), activity (intelligibility and naturalness, [24,27,29,30]) and participation and communication confidence [27,28,31]. There is thus mounting evidence that speech intervention can have benefits both for speech and wider communication impact in people with progressive ataxias.…”
Section: Introductionmentioning
confidence: 99%
“…The results for the intelligibility component were promising for reading and in line with other therapies [24, 27, 29]. The results were less clear for the monologue task where only some speakers showed improvements and group statistics were not significant.…”
Section: Discussionmentioning
confidence: 71%
“…Together these studies have highlighted a range of potential communication benefits across all areas of the International Classification of Functioning and Disability (ICF) model, i.e., impairment (e.g. breath support, voice quality, loudness [23][24][25][26][27][28]), activity (intelligibility and naturalness, [24,27,29]) and participation [27,28]. There is thus mounting evidence that speech intervention can have benefits both for speech and wider communication impact in people with progressive ataxias.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for ataxic speech problems, as opposed to Parkinsonian symptoms which have been investigated much more widely. However, a number of trials have recently been reported that focused on people with MSA-C [8][9][10], in addition to studies on other types of progressive ataxias which can lead to similar speech problems [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%